2021
DOI: 10.2196/25099
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Workplace-Based HIV Self-testing on Uptake of Testing and Linkage to HIV Care or Prevention by Men in Uganda (WISe-Men): Protocol for a Cluster Randomized Trial

Abstract: Background HIV testing uptake remains low among men in sub-Saharan Africa. HIV self-testing (HIVST) at the workplace is a novel approach to increase the availability of, and access to, testing among men. However, both access and linkage to posttest services remain a challenge. Objective The aim of this protocol is to describe a cluster randomized trial (CRT)—Workplace-Based HIV Self-testing Among Men (WISe-Men)—to evaluate the effect of HIVST in workpla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The study was an explorative narrative study within the Workplace-Based HIV Self-testing among Men (WISe-Men) clinical trial. The protocol for the trial is presented elsewhere [ 36 ]. This was a two-arm cluster randomized trial (CRT) involving men employed in private security services in Uganda (clinicaltrials.gov registration number NCT04164433).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was an explorative narrative study within the Workplace-Based HIV Self-testing among Men (WISe-Men) clinical trial. The protocol for the trial is presented elsewhere [ 36 ]. This was a two-arm cluster randomized trial (CRT) involving men employed in private security services in Uganda (clinicaltrials.gov registration number NCT04164433).…”
Section: Methodsmentioning
confidence: 99%
“…Men contribute about 11,000 of the new HIV infections in Uganda and about 10,000 AIDS-related deaths among people above 15 years of age [ 16 ]. A study among men employed in security companies revealed that several of them have multiple sexual partners which may increase their risk of HIV [ 17 ]. Similarly, a study in southern Uganda among key and priority populations reported that PrEP uptake was low and those who were initiated were more likely to discontinue usage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The descriptive qualitative study was conducted as part of the W orkplace-based H I V Se lf-testing among Men (WISe-Men), Cluster randomized trial (Clinical trials.gov ID NCT04164433) ( 20 ). In the WISe-Men trial, men working in private security services in two Ugandan districts were offered HIV self-testing or standard HIV testing services at their workplaces.…”
Section: Methodsmentioning
confidence: 99%
“…Third, feasibility and acceptability are multifaceted concepts for which the field of implementation research has yet to establish standard, validated metrics and definitions; thus, we captured diverse assessments for these outcomes in the review. Fourth, the review was limited to HIVST use for PrEP initiation and continuation and did not include the many interventions that have used HIVST to support linkage to PrEP services [39] or facilitate HIV testing among sexual partners [40][41][42] or peers [43]. Fifth, we only included English and peer-reviewed publications, and thus may have missed implementation projects that have used HIVST to support PrEP delivery but have not published these findings.…”
Section: Evidence Summarymentioning
confidence: 99%